The Influence Of Job Analysis And Job Evaluation On Employee Performance Through Work Motivation At The District Office In Bondowoso Regency: English - Trio Akbar Pamungkas; Suwignyo Widagdo; Muhaimin Dimyati (Yayasan Pendidikan Belajar Berdikari, 2025)
The problem that is the focus of this research is the sub-optimal performance of District Office employees in Bondowoso. The important factors raised to answer this problem are job analysis and job evaluation with motivation as an intervening variable. So the aim of this research is to determine and analyze the influence of job analysis and job evaluation on the performance of sub-district office employees in Bondowoso through motivation as an intervening variable. The research method used is descriptive and quantitative. The population in this study was structural officials (Goals III and IV) totaling 184 employees. The population used was 92 respondents. The sampling technique used in this research is non probability sampling, namely the purposive sampling method. The data analysis technique used is path analysis operated using SPSS 22.0. The test results prove that job analysis and evaluation have a significant effect on the work motivation of District Office employees throughout Bondowoso Regency. Furthermore, job analysis and evaluation and work motivation have a significant effect on the performance of District Office employees throughout Bondowoso Regency. Lastly, job analysis and evaluation influence employee performance through work motivation in District Offices throughout Bondowoso Regency